Comparison of cognitive achievement model: teacher learning character and student learning character with school climate moderation, PLSPredick approach - Abukasim, Sudarto M.; Sutrisno, Hari; Rohaeti, Eli (Frontiers in Education, 2025)
This study examines the interaction between teacher learning character, student learning character, and school climate in influencing students’ cognitive achievement. Data from 1,057 high school students in North Maluku was analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. This study explores the direct relationship and mediation between variables. The results showed that teacher competence and innovation significantly improved teacher efficacy (R2 = 0.576) and teacher performance (R2 = 0.670) despite its direct influence on students’ low cognitive achievement (R2 = 0.024). In contrast, student character, such as learning style, learning concepts, and academic perseverance, had a more direct and mediating influence on cognitive outcomes, with academic perseverance as the primary mediator. In addition, the school climate moderates the relationship between teacher innovation and cognitive achievement, which shows a selective yet essential role. These findings emphasize the importance of encouraging teacher innovation, increasing student perseverance, and building a supportive school environment to optimize educational outcomes. This study highlights the complexity of the interaction between teaching, learning, and environmental factors and suggests the need for integrated strategies to improve students’ cognitive achievement.